Dual-doped coated lithium iron phosphate positive electrode material and preparation method thereof, and lithium battery

By using a metal organic frame and a composite carbon source for double doping coating in the lithium iron phosphate positive electrode material, the problems of its low electronic conductivity and lithium ion diffusion rate are solved, and the specific capacity and cycling performance of the material are significantly improved.

CN119008918BActive Publication Date: 2025-01-17HUNAN YUNENG NEW ENERGY BATTERY MATERIALS CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411479146.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-10-23
Publication Date
2025-01-17
Estimated Expiration
2044-10-23

AI Technical Summary

Technical Problem

The low electronic conductivity and low lithium ion diffusion rate of lithium iron phosphate cathode material lead to poor specific capacity and cycling performance.

Method used

The metal organic frame and composite carbon source are used for double doping coating. The specific steps include reacting the N and S co-doped iron-based metal organic frame with LiH2PO4 to form an intermediate product, and carbon is carried out with lignin nanosilver composite and glucose. Coated to form a lithium iron phosphate positive electrode material with high conductivity and good circulation performance.

Benefits of technology

The electronic conductivity and cycle stability of lithium iron phosphate positive electrode material have been significantly improved, and high specific capacity and excellent electrochemical performance have been achieved. The first discharge specific capacity is 161.6-163.8mAh·g-1, and discharge is after 100 weeks of circulation. The specific capacity is 155.7-158.2mAh·g-1.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119008918B_ABST
    Figure CN119008918B_ABST
Patent Text Reader

Abstract

The invention discloses a dual-doped coated lithium iron phosphate positive electrode material and a preparation method thereof, and a lithium battery, belonging to the technical field of lithium batteries. The dual-doped coated lithium iron phosphate positive electrode material is a lithium iron phosphate positive electrode material obtained by adding a metal organic framework and a composite carbon source for modification, the metal organic framework is a N and S co-doped iron-based metal organic framework, and the composite carbon source includes a lignin nano-silver complex and glucose. The preparation method is as follows: a solid obtained by calcining a dispersed mixture of the metal organic framework and LiH2PO4 to obtain an intermediate product; the lignin nano-silver complex, glucose and the intermediate product are mixed, filtered, dried and calcined. The invention uses the N and S co-doped iron-based metal organic framework as an iron source, and uses the lignin nano-silver complex and glucose as a composite carbon source to prepare the dual-doped coated lithium iron phosphate positive electrode material, which has a higher specific capacity and better cycle performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of lithium batteries, and in particular relates to a dual-doped coated lithium iron phosphate positive electrode material and a preparation method thereof, and a lithium battery. Background Art

[0002] Lithium-ion batteries have the advantages of high energy density, small memory effect, and slow charging loss during use. The performance and cost of lithium-ion batteries are mainly determined by the positive electrode materials. Therefore, people continue to deepen their research on positive electrode materials. Among many positive electrode materials, lithium iron phosphate (LiFePO4) is widely recognized for its advantages such as low cost, long cycle life and high safety. However, LiFePO4 positive electrode materials also have the disadvantages of low electronic conductivity and low lithium ion diffusion rate, resulting in poor specific capacity and cycle performance of the prepared positive electrode materials. Therefore, the materials need to be improved. The current improvement methods are mainly ion doping, surface carbon coating, particle size and morphology control, etc., but the performance of the obtained lithium iron phosphate positive electrode materials is still not ideal. Summary of the invention

[0003] In order to overcome the problem of poor performance of lithium iron phosphate positive electrode materials in the prior art, one of the objectives of the present invention is to provide a dual-doped coated lithium iron phosphate positive electrode material, which has higher specific capacity and cycle stability.

[0004] The second object of the present invention is to provide a method for preparing a dual-doped coated lithium iron phosphate positive electrode material.

[0005] A third object of the present invention is to provide a lithium battery.

[0006] In order to achieve the above-mentioned purpose, the present invention provides a dual-doped coated lithium iron phosphate positive electrode material, which is a lithium iron phosphate positive electrode material obtained after modification by adding a metal organic framework and a composite carbon source, wherein the metal organic framework is a N and S co-doped iron-based metal organic framework, and the composite carbon source includes a lignin nano-silver complex and glucose.

[0007] The present invention also provides a method for preparing a dual-doped coated lithium iron phosphate positive electrode material, comprising the following steps:

[0008] S1. Dispersing the metal organic framework in anhydrous ethanol to obtain a suspension, dispersing LiH2PO4 in anhydrous ethanol to obtain a LiH2PO4 solution, and dropping the LiH2PO4 solution into the suspension under stirring conditions. After the dropping is completed, stirring and reacting at room temperature for 24 hours, and then evaporating at 80°C. The dried solid is transferred to a tube furnace, heated to 600°C at a heating rate of 2°C / min under a reducing atmosphere, and then calcined for 5 hours to obtain an intermediate product.

[0009] S2. The lignin nanosilver complex, glucose and the intermediate product are dispersed in anhydrous ethanol at the same time, stirred at 60°C for 24 hours, filtered, the filter cake is dried at 120°C for 10 hours, transferred to a tubular furnace, and pre-burned at 300-400°C for 5 hours at a heating rate of 10°C / min under nitrogen protection, and then calcined at a constant temperature of 680-800°C for 6-14 hours at a heating rate of 5°C / min, and finally cooled to room temperature at a cooling rate of 10°C / min to obtain a dual-doped coated lithium iron phosphate positive electrode material.

[0010] The present invention first uses a metal organic framework as an iron source and reacts it with LiH2PO4 to prepare an intermediate product. During the roasting process, the organic ligands inside the metal organic framework are pyrolyzed into a carbon network skeleton, and play a bridging role to connect LiFePO4 nanoparticles. The connection can greatly improve the conductivity between LiFePO4 particles. The pyrolysis process causes a large number of mutually cross-linked pore structures to exist inside the intermediate product. The pore structure can provide a large number of channels for the injection of electrolyte, thereby increasing the direct contact area between the electrolyte and the LiFePO4 particles, shortening the diffusion distance of lithium ions in the electrolyte, and being beneficial to the improvement of the electrochemical performance of the LiFePO4 material. In addition, the carbon network skeleton can be used as a solid support to support the LiFePO4 nanoparticles, preventing the LiFePO4 nanoparticles from agglomerating during the charge and discharge process, so as to alleviate the damage to the material body structure caused by the volume change of the two crystal phases of LiFePO4 and FePO4 during the long-term charge and discharge process, and is beneficial to the improvement of the cycle stability performance of the LiFePO4 material.

[0011] More importantly, the metal organic framework of the present invention is a N and S co-doped iron-based metal organic framework (derived from 1,2-benzisothiazol-3-one), and the carbon network skeleton formed by pyrolysis contains nitrogen and sulfur elements, which can not only provide the conductivity of the material, but also reduce the energy barrier for ion penetration, and can further increase the electrochemical performance of the LiFePO4 material;

[0012] Afterwards, the present invention uses lignin nano-silver complex and glucose as composite carbon sources to carbon-coat the intermediate product. Both the lignin nano-silver complex and glucose have good dispersibility. The carbon layer formed by the pyrolysis of the lignin nano-silver complex contains conductive silver ions, which synergistically enhance the electrochemical properties of the material and exhibit good cycle performance.

[0013] Furthermore, the mass ratio of the metal organic framework and LiH2PO4 in S1 is 8.67-9.53:4.08, the dosage ratio of the metal organic framework and anhydrous ethanol in the suspension is 8.67-9.53g:100mL, and the dosage ratio of LiH2PO4 and anhydrous ethanol in the LiH2PO4 solution is 4.08g:100mL.

[0014] Furthermore, the reducing atmosphere in S1 is composed of hydrogen and argon in a mass ratio of 1:9.

[0015] Furthermore, the usage ratio of the lignin nanosilver complex, glucose, the intermediate product and anhydrous ethanol in S2 is 1-3g:3-4g:100g:1L.

[0016] Furthermore, the preparation method of the metal organic framework comprises the following steps:

[0017] FeCl3·6H2O, terephthalic acid, and 1,2-benzisothiazol-3-one were added to a mixed solvent consisting of DMF and acetic acid, and after ultrasonic dispersion, the mixture was transferred to an oil bath and treated at 150°C for 1 h. The mixture was then centrifuged and the precipitate was washed three times with DMF and finally dried under vacuum at 60°C for 12 h.

[0018] The dosage ratio of FeCl3·6H2O, terephthalic acid, 1,2-benzisothiazol-3-one and mixed solvent is 12 mg:38.2 mg:30-50 mg:5.264 mL, the volume ratio of DMF and acetic acid in the mixed solvent is 5:0.264, and FeCl3·6H2O is used as the metal salt, terephthalic acid is used as the organic ligand, 1,2-benzisothiazol-3-one is used as the doping ligand, and acetic acid is used as the regulating agent to prepare N, S co-doped iron-based metal organic framework, namely the above-mentioned metal organic framework.

[0019] Furthermore, the preparation method of the lignin nano-silver composite comprises the following steps:

[0020] The alkaline lignin was dispersed in anhydrous ethanol, stirred for 8 hours, and then the solid and liquid were separated, and the filtrate was dried to obtain ethanol-extracted lignin;

[0021] The ethanol-extracted lignin was dissolved in anhydrous ethanol to obtain a mother liquor with a concentration of 10 mg / mL. The mother liquor was added to an ethanol aqueous solution and the pH value was adjusted to 8-10 with NaOH. Then, a silver nitrate solution was added and reacted under ultraviolet irradiation for 30 minutes. Finally, the reaction product was placed in a dialysis bag and dialyzed in deionized water for 3 days, and finally freeze-dried.

[0022] Firstly, anhydrous ethanol is used to extract and separate the ethanol-extracted lignin with a smaller molecular weight and a higher phenolic hydroxyl content in the alkaline lignin. Then, the ethanol-extracted lignin is used as a reducing agent and a dispersing carrier to prepare a lignin nanosilver composite under ultraviolet light. The preparation process is simple and green.

[0023] Furthermore, the usage ratio of alkaline lignin and anhydrous ethanol in the preparation process of ethanol extraction lignin is 50g:10L.

[0024] Furthermore, the volume ratio of the mother liquor, the ethanol aqueous solution and the silver nitrate solution is 0.7:68.6:0.7, the mass fraction of the ethanol aqueous solution is 40-60%, and the concentration of the silver nitrate solution is 0.0927 mol / L.

[0025] Furthermore, the UV intensity is 40 mW / cm 2 , the ultraviolet wavelength is 365nm.

[0026] Furthermore, the molecular weight cut-off of the dialysis bag is 100-500Da.

[0027] The present invention also provides a lithium battery, comprising a positive electrode, a negative electrode, an electrolyte and a separator, wherein the positive electrode is made of the dual-doped coated lithium iron phosphate positive electrode material.

[0028] Beneficial effects of the present invention:

[0029] The invention uses N and S co-doped iron-based metal organic framework as an iron source, and uses lignin nano-silver composite and glucose as a composite carbon source to prepare a dual-doped coated lithium iron phosphate positive electrode material. The N and S co-doping, metal organic framework and carbon coating jointly improve the conductivity of the material and promote the diffusion of lithium ions, so that the final lithium iron phosphate positive electrode material has a higher specific capacity and better cycle performance, which is ultimately reflected in the first discharge specific capacity of 161.6-163.8 mAh·g at a discharge current of 0.1C. -1 After 100 cycles, the discharge capacity is 155.7-158.2 mAh g -1 . BRIEF DESCRIPTION OF THE DRAWINGS

[0030] The present invention will be further described below in conjunction with the accompanying drawings.

[0031] Figure 1 This is a schematic electron microscope diagram of the dual-doped coated lithium iron phosphate positive electrode material of Example 1;

[0032] Figure 2 This is a schematic diagram of the EDS surface scan of the N element in the dual-doped coated lithium iron phosphate positive electrode material of Example 1;

[0033] Figure 3 This is a schematic diagram of the EDS surface scan of the S element in the dual-doped coated lithium iron phosphate positive electrode material of Example 1;

[0034] Figure 4 This is a schematic diagram of the EDS surface scan of the Ag element in the dual-doped coated lithium iron phosphate positive electrode material of Example 1. DETAILED DESCRIPTION

[0035] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0036] The alkaline lignin in this application was purchased from Xinyi Feihuang Chemical Co., Ltd.

[0037] Preparation Example 1

[0038] A metal organic framework comprises the following preparation steps:

[0039] 12 mg FeCl3·6H2O, 38.2 mg terephthalic acid and 30 mg 1,2-benzisothiazol-3-one were added to a mixed solvent consisting of 5 mL DMF and 0.264 mL acetic acid. After ultrasonic dispersion for 10 min, the mixture was transferred to an oil bath and treated at 150 °C for 1 h. After centrifugation, the precipitate was washed three times with DMF and finally dried in vacuum at 60 °C for 12 h.

[0040] Preparation Example 2

[0041] A metal organic framework comprises the following preparation steps:

[0042] 12 mg FeCl3·6H2O, 38.2 mg terephthalic acid and 40 mg 1,2-benzisothiazol-3-one were added to a mixed solvent consisting of 5 mL DMF and 0.264 mL acetic acid, and ultrasonically dispersed for 15 min. Then the mixture was transferred to an oil bath and treated at 150 °C for 1 h. The mixture was then centrifuged and the precipitate was washed three times with DMF and finally dried in vacuum at 60 °C for 12 h.

[0043] Preparation Example 3

[0044] A metal organic framework comprises the following preparation steps:

[0045] 12 mg FeCl3·6H2O, 38.2 mg terephthalic acid and 50 mg 1,2-benzisothiazol-3-one were added to a mixed solvent consisting of 5 mL DMF and 0.264 mL acetic acid. After ultrasonic dispersion for 20 min, the mixture was transferred to an oil bath and treated at 150 °C for 1 h. The mixture was then centrifuged and the precipitate was washed three times with DMF and finally dried in vacuum at 60 °C for 12 h.

[0046] Comparative Example 1

[0047] A metal organic framework, the preparation steps are the same as those of Example 2 except that 1,2-benzisothiazol-3-one in Example 2 is replaced by an equimolar amount of indolin-1-one.

[0048] Comparative Example 2

[0049] A metal organic framework, the preparation steps are the same as those of Example 2 except that 1,2-benzisothiazol-3-one and acetic acid in Example 2 are removed.

[0050] Example 1

[0051] A method for preparing a dual-doped coated lithium iron phosphate positive electrode material comprises the following steps:

[0052] S1. Disperse 8.67 g of the metal organic framework of Preparation Example 2 in 100 mL of anhydrous ethanol to obtain a suspension, disperse 4.08 g of LiH2PO4 in 100 mL of anhydrous ethanol to obtain a LiH2PO4 solution, and drop the LiH2PO4 solution into the suspension under stirring at 100 rpm. After the dropwise addition is completed, stir at room temperature for 24 h and evaporate to dryness at 80 ° C. The dried solid is transferred to a tubular furnace, and in a reducing atmosphere, the reducing atmosphere is composed of hydrogen and argon in a mass ratio of 1:9, and the temperature is increased to 600 ° C at a heating rate of 2 ° C / min and then calcined for 5 h to obtain an intermediate product;

[0053] S2. Disperse 3 g of lignin nanosilver complex, 3 g of glucose and 100 g of the intermediate product in 1 L of anhydrous ethanol at the same time, stir at 60 ° C for 24 h, filter with suction, dry the filter cake at 120 ° C for 10 h, transfer it to a tubular furnace, and under nitrogen protection, heat it to 300 ° C at a heating rate of 10 ° C / min for pre-burning for 5 h, then heat it at a constant temperature of 680 ° C for 14 h at a heating rate of 5 ° C / min, and finally cool it to room temperature at a cooling rate of 10 ° C / min to obtain a dual-doped coated lithium iron phosphate positive electrode material.

[0054] The preparation method of the lignin nano-silver composite comprises the following steps:

[0055] Disperse 50 g of alkaline lignin in 10 L of anhydrous ethanol, stir for 8 h, separate the solid and liquid, and dry the filtrate to obtain ethanol-extracted lignin;

[0056] The ethanol-extracted lignin was dissolved in anhydrous ethanol to obtain a mother liquor with a concentration of 10 mg / mL. 0.7 mL of the mother liquor was added to 68.6 mL of a 40 wt% ethanol aqueous solution, and the pH value was adjusted to 8 with NaOH. Then, 0.7 mL of a 0.0927 mol / L silver nitrate solution was added and the mixture was reacted for 30 min under ultraviolet irradiation at an ultraviolet intensity of 40 mW / cm 2, the ultraviolet wavelength is 365nm, and finally the reaction product is placed in a dialysis bag and dialyzed in deionized water for 3 days. The molecular weight cutoff of the dialysis bag is 100Da, and finally it is freeze-dried.

[0057] like Figures 1 to 4 As shown, Figure 1 This is a schematic electron microscope diagram of the dual-doped coated lithium iron phosphate positive electrode material of Example 1; Figure 2 , 3 4 are schematic EDS scans of N, S and Ag elements in the dual-doped coated lithium iron phosphate positive electrode material of Example 1.

[0058] Example 2

[0059] A method for preparing a dual-doped coated lithium iron phosphate positive electrode material comprises the following steps:

[0060] S1. Disperse 9 g of the metal organic framework of Preparation Example 1 in 100 mL of anhydrous ethanol to obtain a suspension, disperse 4.08 g of LiH2PO4 in 100 mL of anhydrous ethanol to obtain a LiH2PO4 solution, and drop the LiH2PO4 solution into the suspension under stirring at 150 rpm. After the dropwise addition is completed, react at room temperature with stirring for 24 h and then evaporate to dryness at 80 ° C. The dried solid is transferred to a tubular furnace, and in a reducing atmosphere, the reducing atmosphere is composed of hydrogen and argon in a mass ratio of 1:9, and the temperature is increased to 600 ° C at a heating rate of 2 ° C / min, and then calcined for 5 h to obtain an intermediate product;

[0061] S2. Disperse 3g of lignin nanosilver complex, 4g of glucose and 100g of the intermediate product in 1L of anhydrous ethanol at the same time, stir at 60°C for 24h, filter with suction, dry the filter cake at 120°C for 10h, transfer it to a tubular furnace, and under nitrogen protection, heat it to 350°C at a heating rate of 10°C / min for pre-burning for 5h, then heat it at 730°C at a constant temperature of 5°C / min for 10h, and finally cool it to room temperature at a cooling rate of 10°C / min to obtain a dual-doped coated lithium iron phosphate positive electrode material.

[0062] The preparation method of the lignin nano-silver composite comprises the following steps:

[0063] Disperse 50 g of alkaline lignin in 10 L of anhydrous ethanol, stir for 8 h, separate the solid and liquid, and dry the filtrate to obtain ethanol-extracted lignin;

[0064] The ethanol-extracted lignin was dissolved in anhydrous ethanol to obtain a mother liquor with a concentration of 10 mg / mL. 0.7 mL of the mother liquor was added to 68.6 mL of a 50 wt% ethanol aqueous solution, and the pH value was adjusted to 9 with NaOH. Then, 0.7 mL of a 0.0927 mol / L silver nitrate solution was added and the mixture was reacted for 30 min under ultraviolet irradiation at an ultraviolet intensity of 40 mW / cm2 , the ultraviolet wavelength is 365nm, and finally the reaction product is placed in a dialysis bag and dialyzed in deionized water for 3 days. The molecular weight cutoff of the dialysis bag is 300Da, and finally freeze-dried.

[0065] Example 3

[0066] A method for preparing a dual-doped coated lithium iron phosphate positive electrode material comprises the following steps:

[0067] S1. Disperse 9.53 g of the metal organic framework of Preparation Example 3 in 100 mL of anhydrous ethanol to obtain a suspension, disperse 4.08 g of LiH2PO4 in 100 mL of anhydrous ethanol to obtain a LiH2PO4 solution, and drop the LiH2PO4 solution into the suspension under stirring at 200 rpm. After the dropwise addition is completed, stir at room temperature for 24 h and evaporate to dryness at 80 ° C. The dried solid is transferred to a tubular furnace, and in a reducing atmosphere, the reducing atmosphere is composed of hydrogen and argon in a mass ratio of 1:9, and the temperature is increased to 600 ° C at a heating rate of 2 ° C / min and then calcined for 5 h to obtain an intermediate product;

[0068] S2. Disperse 1g of lignin nanosilver complex, 3g of glucose and 100g of the intermediate product in 1L of anhydrous ethanol at the same time, stir at 60°C for 24h, filter with suction, dry the filter cake at 120°C for 10h, transfer it to a tubular furnace, and under nitrogen protection, heat it to 400°C at a heating rate of 10°C / min for pre-burning for 5h, then heat it at 800°C at a constant temperature of 5°C / min for 6h, and finally cool it to room temperature at a cooling rate of 10°C / min to obtain a dual-doped coated lithium iron phosphate positive electrode material.

[0069] The preparation method of the lignin nano-silver composite comprises the following steps:

[0070] Disperse 50 g of alkaline lignin in 10 L of anhydrous ethanol, stir for 8 h, separate the solid and liquid, and dry the filtrate to obtain ethanol-extracted lignin;

[0071] The ethanol-extracted lignin was dissolved in anhydrous ethanol to obtain a mother liquor with a concentration of 10 mg / mL. 0.7 mL of the mother liquor was added to 68.6 mL of a 60 wt% ethanol aqueous solution, and the pH value was adjusted to 10 with NaOH. Then, 0.7 mL of a 0.0927 mol / L silver nitrate solution was added and the mixture was reacted for 30 min under ultraviolet irradiation at an ultraviolet intensity of 40 mW / cm 2 , the ultraviolet wavelength is 365nm, and finally the reaction product is placed in a dialysis bag and dialyzed in deionized water for 3 days. The molecular weight cutoff of the dialysis bag is 500Da, and finally freeze-dried.

[0072] Comparative Example 1

[0073] A method for preparing a dual-doped coated lithium iron phosphate positive electrode material. Compared with Example 1, except that the metal organic framework in Example 1 is replaced by a product prepared in Control Example 1 of equal quality, the remaining steps are the same as those in Example 1.

[0074] Comparative Example 2

[0075] A method for preparing a dual-doped coated lithium iron phosphate positive electrode material, compared with Example 1, except that the metal organic framework in Example 1 is replaced by a product prepared in Control Example 2 of equal mass, the remaining steps are the same as those in Example 1.

[0076] Comparative Example 3

[0077] A method for preparing a dual-doped coated lithium iron phosphate positive electrode material. Compared with Example 1, the preparation steps are the same as those in Example 1 except that the lignin nano-silver composite is replaced with an equal mass of alkali lignin.

[0078] Comparative Example 4

[0079] A method for preparing a dual-doped coated lithium iron phosphate positive electrode material. The preparation steps are compared with those in Example 1, except that glucose is replaced by an equal mass of a lignin nano-silver composite. The preparation method of the lignin nano-silver composite is the same as that in Example 1, and the remaining steps are the same as those in Example 1.

[0080] Comparative Example 5

[0081] A method for preparing a dual-doped coated lithium iron phosphate positive electrode material. Compared with Example 1, the preparation steps are the same as those in Example 1 except that the lignin nano-silver composite is replaced with an equal mass of glucose.

[0082] The dual-doped coated lithium iron phosphate positive electrode materials obtained in Examples 1-3 and Comparative Examples 1-5 were subjected to conductivity tests, specifically using a four-probe tester. Before the test, 0.15 g of the sample to be tested was weighed and pressed into a cylinder with a diameter of 12 mm at 5 MPa. Each sample was measured three times at different positions, and the average value calculated was the final value of the electronic conductivity of the sample, as shown in Table 1:

[0083]

[0084] It can be seen from the data recorded in Table 1 that the electronic conductivity of the lithium iron phosphate positive electrode material obtained in Examples 1-3 is 9.4-9.8×10 -2 S cm -1, which is significantly higher than that of Comparative Examples 1-5, indicating that the lithium iron phosphate positive electrode material prepared by the present invention has a higher electrical conductivity. It can be seen from the test results in Example 1 and Comparative Examples 1 and 2 that the lithium iron phosphate positive electrode material prepared by the metal organic framework prepared with 1,2-benzisothiazol-3-one as the doping ligand has better electrical conductivity. It can be seen from the test results of Example 1 and Comparative Example 3 that the use of alkaline lignin instead of the lignin nano-silver composite and the absence of nano-silver will cause the reduction of the electrical conductivity of the lithium iron phosphate positive electrode material. It can be seen from the test results of Example 1 and Comparative Examples 4 and 5 that the use of lignin nano-silver composite or glucose alone as the coating carbon source is significantly lower than the use of lignin nano-silver composite and glucose as the coating carbon source, which proves that the lignin nano-silver composite and glucose can play a synergistic role in enhancing the electronic conductivity of the lithium iron phosphate positive electrode material.

[0085] The dual-doped coated lithium iron phosphate positive electrode materials obtained in Examples 1-3 and Comparative Examples 1-5 were used as positive electrode active materials, acetylene black was used as a conductive agent, and polyvinylidene fluoride (PVDF) was used as a binder. The positive electrode active material: conductive agent: binder = 85:10:5 were mixed according to a mass ratio, N-methylpyrrolidone (NMP) was added and stirred evenly, and coated on aluminum foil to make a positive electrode sheet, which was vacuum dried at 80°C in a vacuum drying oven for 8h. A metal lithium sheet was used as a negative electrode, a polypropylene microporous membrane (Celgard 2400) was used as a diaphragm, and a 1 mol / L LiPF6 mixed solution was used as an electrolyte. The solvent in the electrolyte was ethylene carbonate (EC) and diethyl carbonate (DEC), and the volume ratio of EC to DMC was 1:1. A button battery was assembled in an argon-filled glove box, and a charge and discharge cycle test was performed using a battery programmable tester. The voltage range was 2.0-3.8V, and the test results are shown in Table 2:

[0086]

[0087] It can be seen from the test results in Table 2 that the lithium iron phosphate materials prepared in Examples 1-3 have a first discharge specific capacity of 161.6-163.8 mAh·g at a discharge current of 0.1 C. -1 After 100 cycles, the discharge capacity is 155.7-158.2 mAh g -1 , indicating that the lithium iron phosphate material prepared by the present invention has higher specific capacity and cycle stability. It can be seen from the test results of Examples 1-3 and Comparative Examples 1-6 that the dual-doped coated lithium iron phosphate positive electrode material prepared by using N and S co-doped iron-based metal organic framework as iron source and lignin nano-silver composite and glucose as composite carbon source has better electrochemical performance.

[0088] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device.

[0089] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A method for preparing a dual-doped coated lithium iron phosphate positive electrode material, characterized in that: The following steps are involved: S1. Dispersing the metal organic framework in anhydrous ethanol to obtain a suspension, dispersing LiH2PO4 in anhydrous ethanol to obtain a LiH2PO4 solution, and dropping the LiH2PO4 solution into the suspension under stirring conditions. After the dropping is completed, stirring at room temperature for 24 hours and then evaporating at 80°C. The dried solid is transferred to a tubular furnace and calcined at 600°C for 5 hours under a reducing atmosphere to obtain an intermediate product. S2, dispersing the lignin nanosilver complex, glucose and the intermediate product in anhydrous ethanol at the same time, stirring at 60°C for 24 hours, filtering with suction, drying the filter cake at 120°C for 10 hours, transferring it to a tubular furnace, pre-calcining it at 300-400°C for 5 hours under nitrogen protection, calcining it at a constant temperature of 680-800°C for 6-14 hours, and cooling it to room temperature to obtain a dual-doped coated lithium iron phosphate positive electrode material; The mass ratio of metal organic framework and LiH2PO4 in S1 is 8.67-9.53:4.08, the amount ratio of metal organic framework and anhydrous ethanol in the suspension is 8.67-9.53g:100mL, and the amount ratio of LiH2PO4 and anhydrous ethanol in the LiH2PO4 solution is 4.08g:100mL; The dosage ratio of lignin nanosilver complex, glucose, intermediate product and anhydrous ethanol in S2 is 1-3 g: 3-4 g: 100 g: 1 L; The dual-doped coated lithium iron phosphate positive electrode material is a lithium iron phosphate positive electrode material obtained by adding a metal organic framework and a composite carbon source for modification, wherein the metal organic framework is a N and S co-doped iron-based metal organic framework, and the composite carbon source includes a lignin nano-silver complex and glucose.

2. The method for preparing a dual-doped coated lithium iron phosphate positive electrode material according to claim 1, characterized in that: The preparation method of a metal organic framework comprises the following steps: FeCl3·6H2O, terephthalic acid and 1,2-benzisothiazol-3-one are added to a mixed solvent consisting of DMF and acetic acid, and the mixture is dispersed by ultrasonication, treated at 150°C for 1 hour, centrifuged, and the precipitate is washed and dried.

3. The method for preparing a dual-doped coated lithium iron phosphate positive electrode material according to claim 2, characterized in that: The dosage ratio of FeCl3·6H2O, terephthalic acid, 1,2-benzisothiazol-3-one and the mixed solvent is 12 mg:38.2 mg:30-50 mg:5.264 mL, and the volume ratio of DMF and acetic acid in the mixed solvent is 5:0.

264.

4. The method for preparing a dual-doped coated lithium iron phosphate positive electrode material according to claim 1, characterized in that: The preparation method of the lignin nano-silver composite comprises the following steps: The alkaline lignin is dispersed in anhydrous ethanol, stirred for 8 hours, and then the solid and liquid are separated, and the filtrate is dried to obtain ethanol-extracted lignin; The ethanol-extracted lignin was dissolved in anhydrous ethanol to obtain a mother liquor with a concentration of 10 mg / mL. The mother liquor was added to an ethanol aqueous solution, and the pH value was adjusted to 8-10. Then, a silver nitrate solution was added and reacted under ultraviolet irradiation for 30 minutes. The reaction product was placed in a dialysis bag and dialyzed in deionized water for 3 days, and finally freeze-dried.

5. The method for preparing a dual-doped coated lithium iron phosphate positive electrode material according to claim 4, characterized in that: The dosage ratio of alkaline lignin to anhydrous ethanol in the preparation process of ethanol extraction lignin is 50g:10L.

6. The method for preparing a dual-doped coated lithium iron phosphate positive electrode material according to claim 4, characterized in that: The volume ratio of the mother liquor, the ethanol aqueous solution and the silver nitrate solution is 0.7:68.6:0.7, and the concentration of the silver nitrate solution is 0.0927 mol / L.

Citation Information

Patent Citations

  • Modified lithium iron phosphate material, preparation method and application thereof

    CN108199041A

  • Preparation method of nitrogen-doped carbon-coated lithium iron phosphate with lignin as source

    CN114373932A